Semiotic Analysis of Symbolic Communication in Li Scraf Hijab with Arabic Newspaper Motif - Nafiul Haliza; Mohamad Madum; Isnaini Isnaini; Agam Maulana; Ananda Maya Damayanti (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
The development of Muslim fashion in Indonesia shows that the hijab is no longer understood solely as a religious obligation, but also as a symbol of identity, lifestyle, and a medium for communicating Islamic values. Through its form, motifs, color, and style of wear, the hijab serves as a means of symbolic communication, conveying social, cultural, and da’wah messages. However, academic studies specifically addressing the hijab as a medium for contemporary da’wah through fashion products, especially local brands, remain limited. This study aims to analyze the symbolic communication contained in the Li Scraf hijab with the Arabic Newspaper motif and to examine consumers’ interpretations of these symbols at Li Boutique Berjan Purworejo. The study employs a qualitative approach, utilizing semiotic analysis of symbolic communication to examine the visual, textual, and symbolic elements of hijab design. The results indicate that the Li Scraf hijab serves as a medium for contemporary da’wah by integrating spiritual messages, religious values, and modern fashion aesthetics. This study enriches Islamic communication and cultural da’wah studies and offers practical implications for the development of an educational and religiously meaningful Muslim fashion industry.